Socio-Cultural Influence on Stunting Incidence in Children Aged 0 – 59 Months In Tarempa Village, Siantan District, Anambas Islands Regency In 2025 - Sitorus, Christ Natalin; Kasim, Felix; Ginting, Desideria Yosepha (CV. Publikasi Indonesia, 2025)
Tarempa Village is a village with the highest stunting rate in Tarempa Village, Siantan District, which is 7.14%. Socio-cultural factors are characteristics of a nation or region that can form patterns of community behavior, which may have an indirect impact on health, derived from hereditary beliefs and traditions. Some of these are in line with health rules, while others are less aligned, and they are involved in their roles within the cultural, social, economic, and health service systems. This study aims to analyze the socio-cultural influence on the incidence of stunting in children aged 0–59 months in Tarempa Village, Siantan District, Anambas Islands Regency. The research sample consisted of 101 parents of toddlers, selected using a purposive sampling technique. The research design used is a Mixed Method. Data collection was carried out using questionnaires and the in-depth interview method. Questionnaire tests were used to guarantee the validity and reliability of the instrument. The study showed a significant influence of cultural, social, and health service systems on the incidence of stunting (p < 0.05) in Tarempa Village, Siantan District, Anambas Islands Regency. There is a significant influence between cultural, social, and health care systems and stunting. The researcher suggested that indigenous leaders should be directly involved in KIE (communicative, informative, and educational) efforts with the community, parents, and the environment, to play an active role in improving children's nutritional status, as well as the involvement of other stakeholders in realizing a qualified health service system.